Low‐sidelobe marine radar microstrip array antenna based on hybrid algorithm and metamaterial - Lin, Kangjian; Fang, Shaojun; Liu, Hongmei (International journal of RF and microwave computer-aided engineering, 2022)
A microstrip array antenna with low sidelobe level (SLL) for X‐band marine radar is proposed. The antenna is composed of a 32‐element patch array and a three‐layer near‐zero‐index metamaterial (NZIM). The IABC‐Kmeans algorithm, which combines the improved artificial bee colony algorithm and K‐means clustering algorithm, is used to optimize the current amplitude of the array elements to obtain a lower SLL. The NZIM is loaded in front of the array antenna to reduce the beamwidth of the E‐plane. The antenna is designed and fabricated. The measurement results show that the gain of the antenna at the center frequency is 22.7 dBi, the SLLs of H‐plane and E‐plane are −30.66 dB and − 26.78 dB respectively, and the half‐power beamwidth of H‐plane is 5.9°. Compared with the previous similar antenna structures, the antenna has lower SLL under the premise of narrow beam and high gain, which is very suitable for X‐band marine radar of small and medium fishing vessels.